2019
DOI: 10.1080/09658211.2019.1616097
|View full text |Cite
|
Sign up to set email alerts
|

The role of event relevance and congruence to social groups in flashbulb memory formation

Abstract: Flashbulb memories are vivid, confidently held, long-lasting memories for the personal circumstances of learning about an important event. Importance is determined, in part, by social group membership. Events that are relevant to one's social group, and furthermore, are congruent with the prior beliefs of that group, should be more likely to be retained as flashbulb memories. The Fukushima nuclear disaster was relevant to ongoing political conversations in both Germany and the Netherlands, but, while the disas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The results obtained are consistent with previous research (Rasmussen and Berntsen, 2009;Talarico et al, 2019) that support Er's (2003) hypothesis, according to which, the relevance given to an event by a certain social group is directly related to maintaining a vivid memory. These results provide a better understanding of how individual memories can contribute to the maintenance and accessibility of historical memories of events with collective and emotionally relevant transcendence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained are consistent with previous research (Rasmussen and Berntsen, 2009;Talarico et al, 2019) that support Er's (2003) hypothesis, according to which, the relevance given to an event by a certain social group is directly related to maintaining a vivid memory. These results provide a better understanding of how individual memories can contribute to the maintenance and accessibility of historical memories of events with collective and emotionally relevant transcendence.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that when a person considers that a public event has great personal consequences or consequences to his/her environment, the person tends to maintain a vivid and consistent memory of the event. Similarly, recent research shows that the events that contribute to the configuration of social identity tend, more likely, to generate FBM (Luminet and Curci, 2009;Talarico et al, 2019). In this direction, several studies have also shown how the age of the participants affects the generation of FBM, as younger people have less ability to assess the consequences or relevance of the events (Denver et al, 2010;Vallet et al, 2017).…”
Section: Fbm Formationmentioning
confidence: 91%
“…FBMs may be unique among autobiographical memories in their increased service of social rather than directive or self‐functions (Rasmussen & Berntsen, 2009); people may be particularly inclined to retrieve a FBM to share and connect with other individuals with similar experiences. Indeed, it has been suggested that FBM formation may occur, in part, due to activation of one's social identity surrounding an event (Berntsen, 2009; Talarico, Bohn, & Wessel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One notable example is research on flashbulb memories. Flashbulb memories are memories about the personal circumstances in which one first learns about a surprising and emotional public event (Conway et al, 1994; Hirst et al, 2018), such as the deaths of public figures (Day & Ross, 2014; Demiray & Freund, 2015; Tinti et al, 2014), political events (e.g., the fall of the Berlin Wall; Bohn & Berntsen, 2007), the resignations of Prime Ministers (e.g., Conway et al, 1994; Stone et al, 2015), the Fukushima nuclear disaster (Talarico et al, 2019), the inauguration of President Obama (Koppel et al, 2013), and sporting events (Breslin & Safer, 2011; Kopietz & Echterhoff, 2014; Merck et al, 2020; Talarico & Moore, 2012; Tinti et al, 2014). In research on flashbulb memories, researchers typically assess how participants learned of an emotional public event shortly after it occurred, followed by a subsequent assessment about the same memory a few months or years later.…”
mentioning
confidence: 99%